Screening for Candidate Hepatic Growth Factors by Selective Portal Infusion after Canine Eck's Fistula - Francavilla, Antonio (1991)
Completely diverting portacaval shunt (Eck's fistula) in dogs causes hepatocyte atrophy, disruption of hepatocyte organelles, fatty infiltration and low-grade hyperplasia. The effect of hepatic growth regulatory substances on these changes was assessed by constantly infusing test substances for four postoperative days after Eck's fistula into the detached left portal vein above the shunt. The directly infused left lobes were compared histopathologically with the untreated right lobes. In what has been called an hepatotrophic effect, stimulatory substances prevented the atrophy and increased hepatocyte mitoses. Of the hormones tested, only insulin was strongly hepatotrophic; T(3) had a minor effect, and glucagon, prolactin, angiotensin II, vasopressin, norepinephrine and estradiol were inert. Insulin-like growth factor, hepatic stimulatory substance, transforming growth factor–α and hepatocyte growth factor (also known as hematopoietin A) were powerfully hepatotrophic, but epidermal growth factor had a barely discernible effect. Transforming growth factor–β was inhibitory, but tamoxifen, interleukin-1 and interleukin-2 had no effect. The hepatotrophic action of insulin was not altered when the insulin infusate was mixed with transforming growth factor–β or tamoxifen. These experiments show the importance of in vivo in addition to in vitro testing of putative growth control factors. They illustrate how Eck's fistula model can be used to screen for such substances and possibly to help delineate their mechanisms of action.